2000
DOI: 10.1002/ls.3010120206
|View full text |Cite
|
Sign up to set email alerts
|

Modern solid lubrication: Recent developments and applications of MoS2

Abstract: An important and growing field of lubrication lies in the use of solid films, although they are in general more expensive than oils or greases, and require specialist attention both in mechanical design and in coating application techniques. In this paper, the general classification of solid lubricant types is reviewed, along with the reasons for choosing, and methods of depositing, solid lubricants, in particular MoS2. The best‐performing and most flexible technique for making MoS2 films is by physical vapour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(48 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…When MoS 2 is in the presence of oxygen, oxidation can occur, resulting in MoO 3 . The proposed wear mechanisms are complicated: superficial oxidation can flake off due to the reduction of the oxide layer through cohesion to the bulk, brittle oxides can delaminate, and/or oxidation can work its way into the bulk of the material, creating internal blisters that act as weak points leading to cracking and greater volumes of debris [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…When MoS 2 is in the presence of oxygen, oxidation can occur, resulting in MoO 3 . The proposed wear mechanisms are complicated: superficial oxidation can flake off due to the reduction of the oxide layer through cohesion to the bulk, brittle oxides can delaminate, and/or oxidation can work its way into the bulk of the material, creating internal blisters that act as weak points leading to cracking and greater volumes of debris [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] MoS 2 is an important solid lubricant because of its exceptional lubricity and the fact that it can easily be coated onto objects by physical vapor deposition (PVD) or chemical vapor deposition (CVD), and forms in-situ by the tribochemical reaction of molybdenum alkyldithiocarbamates, 7-8 the latter which are commonly used additives in lubricating oil formulations. [9][10] Most CVD and PVD processes allow for great flexibility in tuning the chemistry and/or structure of the solid lubricant film, and consequentially tailoring its properties. A number of studies have utilized this method to improve the understanding of the wear behavior of MoS 2 , by altering the bonding between MoS 2 sheets, varying the crystal structure and microstructural length scales, or incorporating oxygen buffers.…”
Section: Introductionmentioning
confidence: 99%
“…MoS 2 is one of the most commonly used solid lubricants for Cu-Fe-based friction materials; it can be used to stabilize friction and improve the wear resistance of composites [6][7][8][9]. However, numerous studies have shown that MoS 2 reacts with Cu or Fe matrices when sintered at temperatures above 950°C [10][11][12][13][14][15][16][17][18][19][20][21]; our recent study revealed that the lubricity of MoS 2 is attributable to the resultant formation of metal sulfides such as FeS [21].…”
Section: Introductionmentioning
confidence: 99%